Effect of powder size on the microstructure and dielectric properties of ZnO ceramics. (August 2015) - Li, Xuhai; Huang, Yuanjie; Xu, Liang; Liu, Lixin; Wang, Yuan; Cao, Xiuxia; Meng, Chuanmin; Wang, Zhigang
Graphical abstract: Highlights: Porous structure ZnO ceramics were achieved using high pressure treated powders. Giant dielectric constant (1.14 × 10 4 at 100 Hz) was achieved for the sample using ∼300 nm powders. Ceramics using different size of powders present apparently different micro-structure. Abstract: Colossal dielectric constant of ZnO has been induced in ceramics prepared by conventional sintering high-pressure treated nano powders. Two different powders (with average sizes of ∼113 nm and ∼336 nm) are performed to better understand the colossal dielectric constant in sintered ZnO. SEM results reveal that the as-achieved ceramics are porous with obviously different microstructure, the grain size and density increases with the increase of powder size. The dielectric permittivity measurements reveal that the appearance of colossal dielectric constant has strong dependence on the size of starting powders. Specimen (with 92% relative density) using ∼336 nm powders presents higher dielectric constants (1.14 × 10 4, at 100 Hz), and keeps a surprisingly high value of 2930 at 1 MHz.